The Short-term efficacy of a monoclonal antibody fragment (brolucizumab) for treating neovascular age-related macular degeneration - A. F. Yusupov; M. Kh. Karimova; S. A. Djamalova; D. K. Makhkamova; S. I. Abdullaeva; M. A. Zakirkhodjaeva; Khodjaeva Zilola; D. A. Rakhimova (Ukrainian Society of Ophthalmologists, 2024)
Aim. To evaluate the short-term efficacy of using a monoclonal antibody fragment (Brolucizumab) for treating neovascular age-related macular degeneration, depending on the morphometric parameters of the retina. Methods: This study included 48 patients (60 eyes) diagnosed with neovascular age-related macular degeneration (nAMD). The observation period was 6 months. Brolucizumab was administered intravitreally at a dose of 6 mg (0.05 ml, 120 mg/ ml) once a month consistently for 3-4 months. Depending on the morphometric parameters, the retina patients were divided into three main groups. Results: A pronounced clinical and morphological response was achieved after the first injection of Brolucizumab, and positive dynamics were observed throughout the entire observation period. Conclusions: The use of the drug Brolucizumab significantly improves the visual functions of patients with neovascular AMD, as well as the morphological state of the retina in short-term follow-up, regardless of the initial morphometric characteristics of the retina, which allows not only to maintain but also to improve visual acuity and prevent blindness and visual disability in patients.